Outsourcing of Public Service Provision: When is it More Efficient? - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
We set up a model of public service provision to study the factors determining whether outsourcing to for-profit and not-for-profit producers of social services will enable a local government to achieve a given service quality at lower budgetary cost. Outsourcing provides an incentive for producers to lower quality in order to reduce costs. The cost reductions per se tend to be efficiency-improving, but to prevent a deterioration of service quality policy makers must spend more resources on monitoring quality. Moreover, the greater effort exerted under private service provision will have to be compensated by higher factor rewards. Hence public in-house provision may be more cost-efficient than outsourcing. This is particularly likely to be the case when the quality of the service is difficult to measure so that marginal monitoring costs are high. The paper shows that these results emerge both when politicians are benevolent and when they distribute rents in exchange for political support. We also show that risk aversion and uncertainty about the potential for cost savings implies a bias against outsourcing.
Keywords: H42; H57; 330; outsourcing; public goods provision; public sector reform; Öffentliche Dienstleistung; Outsourcing